HOW PROJECT-BASED LEARNING SHAPES STUDENTS’ AGENTIC ENGAGEMENT IN EFL CLASSROOM: A MIXED METHODS APPROACH - Muh. Fakhrul Armas; Murni Mahmud; Maemuna Muhayyang; Muh Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Student engagement is crucial for successful learning experiences, encompassing behavioral, cognitive, emotional, and agentic dimensions. In English as a Foreign Language (EFL) learning, engagement directly impacts motivation, language acquisition, and academic performance. Among these, agentic engagement—where students actively control their learning—emerges as a critical yet often overlooked area. This study explores the impact of project-based learning (PjBL) on agentic engagement in EFL classrooms at MAN 1 Soppeng, Indonesia. Using a mixed-methods approach, the research reveals that PjBL significantly enhances students' agentic engagement, particularly in group discussions, responsibility, and independent decision-making. However, challenges persist, such as students' reluctance to communicate directly with teachers. The study found a strong positive correlation (R-value of 0.600) between PjBL and agentic engagement, highlighting the need for strategies that promote proactive student involvement. Future research should explore innovative learning methods and consider factors like family influence and cultural differences to deepen understanding of agentic engagement. These findings contribute to optimizing PjBL for greater student initiative and ownership, enhancing EFL education quality in Indonesia and beyond.